Forecasting Aus Rice Area and Production in Bangladesh using Box-Jenkins Approach (Bangladesh Rice Journal, 2016)
Forecasting of rice area and production is an essential procedure in supporting policy decision regarding food security and environmental issues. The main aim of this paper is to forecast Aus rice area and production in Bangladesh. Box-Jenkins Autoregressive Integrated Moving Average (ARIMA) time-series methodology is considered for modeling and forecasting country's Aus rice area and production data commencing from 1971-72 to 2013-14. It was observed that ARIMA (1, 1, 5) and ARIMA (1, 1, 4) model were performed better than the other ARIMA models for forecasting Aus area and production respectively. The Aus rice areas were forecasted 1041.12 and 499.31 thousand hectares and for production it was 2059.642 and 1781.545 thousand metric tons in 2014-15 and 2023-24 respectively. The forecasted Aus rice area and production both were showed a decreasing trend. Government should create an enabling environment to develop HYV rice varieties for Aus rice crop to ensure ongoing food security by increasing cultivated area and production.Bangladesh Rice j. 2016, 20(1): 1-10